Lécluse-ren Hiztegia: Euskalaritzaren Historiarako Lanabesak (II) - Joseba Andoni Lakarra; Blanka Urgell (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1988)
This article contains an edition of the French-Basque and Basque-French vocabularies which go to make up the second part of the Manuel de la langue basque (1826) by F. Lécluse (L); the first part, grammar, was published in the last issue of ASJU. At the end, we have included the Examen critique du M.L.B. par Lor Urhersigarria (=L). After describing the main characteristics of the vocabularies (size, criteria for admitting terms, documented items of particular interest, etc.), we study some linguistic and graphic details which seem to point to the existence of some literary source used by Lécluse, and examine the items native to Zuberoa that were supplied for the Basque-French vocabulary by Abbadie. We demonstrate with copious evidence that the French-Basque vocabulary in the grammar (1741) by Harriet (H) constitutes the principal source for L's second vocabulary. Although a detailed analysis of H's grammar has been left for a future study, words have been found in it which were used by L and documented in the Supplement (1745) by Larramendi, who was responsible for their coming into wider use; this proves that H constitutes another of the sources of the Supplement together with those named and studied by Mitxelena: Axular, RS and Landuchio. As an appendix to the introduction, we include a Prospectus of the Escuararen Gorputza (The Body of Basque), in which Lécluse describes his larger dictionary which remained unpublished.